2016
DOI: 10.1590/s01518-8787.2016050006723
|View full text |Cite
|
Sign up to set email alerts
|

ERICA: prevalence of dyslipidemia in Brazilian adolescents

Abstract: OBJECTIVE To determine the distribution of total cholesterol, LDL cholesterol, HDL cholesterol, and triglycerides in Brazilian adolescents, as well as the prevalence of altered levels of such parameters.METHODS Data from the Study of Cardiovascular Risks in Adolescents (ERICA) were used. This is a country-wide, school-based cross-sectional study that evaluated 12 to 17-year old adolescents living in cities with over 100,000 inhabitants. The average and distribution of plasma levels of total cholesterol, LDL ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 29 publications
3
32
0
10
Order By: Relevance
“…The Study of Cardiovascular Risk in Adolescents -ERICA was the first nationally represented Brazilian study, designed to provide estimates of the prevalence of diabetes mellitus, obesity, CV risk factors, insulin resistance, and inflammatory markers in adolescents [14][15][16][17]. The present study aims to evaluate the association between WC and elevated BP in adolescents aged 12 to 17 years with a normal BMI.…”
Section: Introductionmentioning
confidence: 99%
“…The Study of Cardiovascular Risk in Adolescents -ERICA was the first nationally represented Brazilian study, designed to provide estimates of the prevalence of diabetes mellitus, obesity, CV risk factors, insulin resistance, and inflammatory markers in adolescents [14][15][16][17]. The present study aims to evaluate the association between WC and elevated BP in adolescents aged 12 to 17 years with a normal BMI.…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obesity are among the main risk factors for the development of Chronic Non-communicable Diseases, and are related to premature death and disability in adult life [2–4]. Studies have shown concerning proportions of dyslipidemia, systemic arterial hypertension, insulin resistance and metabolic syndrome among children and adolescents, which have caused changes in the epidemiological profile of the pediatric population [58]. …”
Section: Introductionmentioning
confidence: 99%
“…As in other studies 37,9 , gender did not influence lipid levels. On the other hand, some studies showed higher mean levels of TC, LDL-C, TG and HDL-C in females 1,38 . The literature shows that in girls a difference in growth and sexual maturation from 14 to 15 years of age can increase lipid levels, including TC 38 .…”
Section: Discussionmentioning
confidence: 96%
“…At early ages, it may cause an atherosclerotic process, and contribute to the development of cardiovascular disease in adulthood. In Brazil, research shows a high prevalence of lipid disorders in adolescence [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%